A Polanyi-inspired perspective on social-ecological transformations of cities - Bärnthaler, Richard; Novy, Andreas; Stadelmann, Basil (Journal of Urban Affairs, 2020)
Based on a Polanyi-inspired research program, we analyze urban transformations as interrelations between infrastructural configurations, i.e. context-dependent material infrastructures and their multi-scalar political-economic regulations, and socio-cultural modes of living. Describing different modes of infrastructure provisioning in Vienna between 1890 and today, we illustrate how political-economic processes of commodification and decommodification have co-evolved with socio-culturally specific modes of living, grounded in different classes and milieus. We show how, today, two modes of living—“traditional,” established during postwar welfare capitalism, and “liberal,” formed during neoliberal capitalism—co-exist. In the current conjuncture of rising inequality, neoliberal urban regeneration, and accelerating climate crisis, these modes of living are not only increasingly polarized and antagonistic, but also increasingly unable to satisfy needs and self-defined aspirations. Therefore, we explore the potential of social-ecological infrastructural configurations as an alliance-building project for a systemic social-ecological transformation, potentially linking different classes, social segments and forces around a common eco-social endeavor.

Re-grounding the city with Polanyi: From urban entrepreneurialism to entrepreneurial municipalism - Thompson, Matthew; Nowak, Vicky; Southern, Alan; Davies, Jackie; Furmedge, Peter (Environment and Planning A: Economy and Space, 2020)
Conventional approaches to local economic development are failing to address deepening polarisation both within and between city regions across advanced capitalist economies. At the same time, austerity urbanism, particularly in the UK, presents challenges for urban authorities facing reduced budgets to meet increased demands on public services. Municipalities are beginning to experiment with creative responses to these crises, such as taking more interventionist and entrepreneurial roles in developing local economies, generating alternative sources of revenue or financialising existing assets. Rooted in a Polanyian perspective and building on the concepts of the entrepreneurial state and grounded city, we identify an embryonic alternative approach – what we call ‘entrepreneurial municipalism’ – as a policy pathway towards resolving enduring socioeconomic problems where neoliberal urban-entrepreneurial strategies have failed. We situate entrepreneurial municipalism as one strand in an assemblage of new municipalist interventions, between radical urban social movements and more neoliberal strategies such as financialised municipal entrepreneurialism. Drawing on original research on the Liverpool City Region, we explore how local authorities are working with social enterprises to harness place-based assets in ways which de-commodify land, labour and capital and re-embed markets back into society. Finally, we draw upon Polanyi as our guide to disentangle differences in approach amongst divergent forms of municipalist statecraft and to critically evaluate entrepreneurial municipalism as a possible trajectory towards the grounded city.
Keywords: Entrepreneurial state; Polanyian economic geography; local economic development; municipal statecraft; urban policy

Where are markets? - Peck, Jamie (Market/Place: Exploring Spaces of Exchange, 2020)
The goal of this chapter is to prepare the ground for theorizing the diversity and spatiality of markets, (necessarily) dealing with, but seeking to move concertedly beyond, the restrictive optic of the orthodox model. It seeks to do so by way of three steps. The following section opens up some preliminary questions about the place of markets and their actually existing historical geography. Next, the chapter turns to the challenge of decentring the market, of moving beyond the idea that the market properly and eternally belongs at the centre of the economic universe. What is the scope for understanding “real markets”, both conceptually and empirically, without recourse to the idealized model of the “pure” market, and all its downstream distortions? Finally, the chapter addresses the question of alternative “mappings” of markets, taking some cues from the work of Karl Polanyi, but urging a more thoroughgoing reconstruction. The chapter’s conclusion acknowledges that the “where?” of markets remains a demanding theoretical question, such that what follows serves to inform some different points of departure, not the destination itself. New answers to this “where?” question, though properly a matter for what Polanyi characterizes as the “substantivist” investigation of real-world market formation, re-formation and transformation, ought to recognize, inter alia: first, the relational character of markets, which are codependent on non-market modes of coordination and regulation; second, their “instituted” form, necessary in function but variable in practice; and not least, third, their always out-of-equilibrium processual dynamics and contradictions.
Keywords: markets; space

Introduction : exploring markets - Peck, Jamie; Berndt, Christian; Rantisi, Norma (Market/Place: Exploring Spaces of Exchange, 2020)
The origin of the present volume was an invitational workshop focused on questions of the spatiality and diversity of markets, held at the Karl Polanyi Institute of Political Economy in Montreal in the summer of 2017. This was an apt meeting place in a more than literal sense. Although many of those in attendance did not subscribe explicitly to a Polanyian worldview or mode of analysis, most had engaged with Polanyi’s work in different ways. Some had made extensive contributions to neo-Polanyian scholarship, while others were more closely affiliated to radical political economy, performativity approaches or poststructuralism. In this context, more pertinent were a series of broadly aligned sympathies with what might be characterized as Polanyian dispositions, including: shared recognition of the importance of respectful, constructive and non-dogmatic exchange across an interdisciplinary range of heterodox and critical positions; overlapping concerns with the potential of empirically engaged and “substantivist” investigation (to borrow the Polanyian terminology), not just in testing and tweaking extant theories but in the construction of new insights, understandings and socio-political visions; and mutual commitments to humane, emancipatory and sustainable modes of socio-economic and ecological development.
Keywords: Karl Polanyi Institute of Political Economy; economic geography; markets